1991
DOI: 10.1084/jem.173.5.1281
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the adhesive capacity of CR3 on neutrophils by endotoxin: dependence on lipopolysaccharide binding protein and CD14.

Abstract: SummaryTumor necrosis factor a, granulocyte colony-stimulating factor, granulocyte/macrophage colonystimulating factor, and formyl peptide were each found to cause a twofold increase in expression of CD14 on the surface of polymorphonuclear leukocytes (PMN). Upregulation of CD14 was complete by 20 min and thus appeared to result from expression of preformed stores ofprotein . The CD14 on the surface ofPMN was shown to serve two biological functions. It bound particles coated with complexes oflipopolysaccharide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
170
2
3

Year Published

1994
1994
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 274 publications
(184 citation statements)
references
References 33 publications
9
170
2
3
Order By: Relevance
“…Some investigators claim that CD14 is expressed in polymorphonuclear neutrophils, although to a lesser extent in monocytes (18), and a positive modulation of CD14 expression on neutrophils by LPS has been reported (20). FACS analysis of the present data showed that the levels of CD14 on unstimulated neutrophils were marginal or absent and, in agreement with Wright et al (21), not affected by LPS stimulation. This absence of significant amounts of CD14 is also indirectly supported by results of an earlier study (22), in which only R-form LPS preparations elicited oxidative responses in isolated neutrophils, while the S-form LPS was virtually inactive.…”
Section: Discussionsupporting
confidence: 79%
“…Some investigators claim that CD14 is expressed in polymorphonuclear neutrophils, although to a lesser extent in monocytes (18), and a positive modulation of CD14 expression on neutrophils by LPS has been reported (20). FACS analysis of the present data showed that the levels of CD14 on unstimulated neutrophils were marginal or absent and, in agreement with Wright et al (21), not affected by LPS stimulation. This absence of significant amounts of CD14 is also indirectly supported by results of an earlier study (22), in which only R-form LPS preparations elicited oxidative responses in isolated neutrophils, while the S-form LPS was virtually inactive.…”
Section: Discussionsupporting
confidence: 79%
“…3B). Some mature neutrophils are also known to express CD14 [30][31][32], however, we have previously shown that IFI 16 is not expressed in these cells [12]. Our two-color cytofluorographic studies were all performed with relatively immature cell populations (e.g., day 7 G-CSF colonies with few mature neutrophils) and we therefore did not see a subpopulation of CD14 ϩ IFI 16 Ϫ neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…CR3 can also bind to LBP (19), and, in the presence of serum and LPS, associate transiently with surface CD14 on the plane of the neutrophil membrane (20). CR4, also a ␤ 2 integrin, is made up by CD18/CD11c and may be involved in transducing LPS signals in the absence of serum (21).…”
Section: ␤ 2 Integrins Are Involved In Cytokine Responses To Wholementioning
confidence: 99%